2014
DOI: 10.1177/0954405414523593
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of wire electrical discharge machining process using evolutionary computation method: Effect of cutting variation

Abstract: This article focuses on comparing the performance of brass wire and zinc-coated brass wire that are widely used as the wire electrode in wire electrical discharge machining. To this end, an evolutionary computation method is presented based on non-dominated sorting genetic algorithm in order to find an optimization of rough cutting of the Ti-6Al-4V titanium alloy with the aid of response surface methodology modeling. This research examines the effects of three process parameters, namely, pulse on-time, pulse o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Also, in low T off time, heat dispersion decreases, causing more heat entrapment and melted material in the surface, which produces thicker white layer. These results are in agreement with other research works as mentioned in the literature review [13,15,16]. Moreover, Ghodsiyeh et al [27] reported that IP and SV have more significant effects on the WLT than the pulse-on time and pulse-off time in WEDM machining of Ti-6Al-4V.…”
Section: White Layer Thickness (Wlt)supporting
confidence: 91%
See 1 more Smart Citation
“…Also, in low T off time, heat dispersion decreases, causing more heat entrapment and melted material in the surface, which produces thicker white layer. These results are in agreement with other research works as mentioned in the literature review [13,15,16]. Moreover, Ghodsiyeh et al [27] reported that IP and SV have more significant effects on the WLT than the pulse-on time and pulse-off time in WEDM machining of Ti-6Al-4V.…”
Section: White Layer Thickness (Wlt)supporting
confidence: 91%
“…A comprehensive literature review has been performed on various aspects of WEDM process and is summarized in table 1. Although several attempts were made to understand the mechanism of formation and properties of the white layer and HAZ, it is evident from the literature review that few research works [10][11][12][13][14][15][16] have been conducted to model the process by correlating the dominant input parameters with the white layer and HAZ depth as the machining performance, especially since it is not easy to identify and measure HAZ.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the studies of several authors was the assumption that the development of microhardness does not need to be the same across the eroded surface, and it was therefore chosen the procedure for implementing measurements in different parts of the eroded surface. 28 Due to the expected very small total depth of the HAZ, which is the order of tens of µm, was created the certain problem in the methodology of measuring microhardness. Because the eroded surface has very small dimensions of 10 × 10 mm 2 , it was not possible to use the bevelled cross-sectional method.…”
Section: Methodsmentioning
confidence: 99%
“…26 It was heat-treated by hardening in air at temperature about 1030°C with subsequent tempering at the temperature about 580°C to the hardness of 53 HRC ( Figure 3). Samples were prepared by pickling in chemical solution Armohib 28 (Akzo Nobel Surface Chemistry AB, Sweden) on the base of H 3 PO 4 with concentration of 15% at constant temperature 40°C with a total duration of action for 10 min. The advantage of using the stain on the base of H 3 PO 4 is the creation of a thin phosphate film which in consequence protects the surface against its re-oxidation with atmospheric oxygen O 2 and H 2 O humidity.…”
Section: Description Of Samples and Devices Used In The Experimentsmentioning
confidence: 99%
“…Response surface methodology (RSM) also helps to find interaction effect among the control parameters on responses. 17 Golshan et al 18 presented a mathematical model using RSM method to optimize the process parameters and analyse the model to signify the process behaviour of WEDM operation.…”
Section: Introductionmentioning
confidence: 99%